2014
DOI: 10.1371/journal.pone.0114499
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Failure and Active Bleeding Are the Important Fatality Predictive Factors for Severe Dengue Viral Infection

Abstract: ObjectiveTo determine the outcome of severe dengue viral infection (DVI) and the main dengue fatality risk factors.Study designThe medical records of patients aged <15 years admitted to Songklanagarind Hospital in southern Thailand during 1989–2011 were reviewed. Patients who had dengue hemorrhagic fever (DHF) grades III–IV, organ failure (cardiovascular, respiratory, liver, renal or hematologic), impaired consciousness, or aspartate aminotransferase more than 1,000 units/L, were classified as having severe DV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 20 publications
0
15
1
Order By: Relevance
“…On the other hand, as an intrinsic abnormality, impaired TLR3-mediated interferon-β (IFN-β)54 and IFN-λ55 production by asthmatic epithelial cells may also predispose to dengue virus indirectly5657. This allergic inflammatory cascade may also play a role in the development of acute respiratory failure, which was reported to be a risk factor of dengue fatal cases27. Future studies will be required to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, as an intrinsic abnormality, impaired TLR3-mediated interferon-β (IFN-β)54 and IFN-λ55 production by asthmatic epithelial cells may also predispose to dengue virus indirectly5657. This allergic inflammatory cascade may also play a role in the development of acute respiratory failure, which was reported to be a risk factor of dengue fatal cases27. Future studies will be required to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Dengue associated severe organ involvement were cardiovascular18, hepatic141920, renal2122, as well as central nervous systems2324, and to some extent, respiratory252627 and muscular systems2829. Different dengue serotypes may have different severe organ involvements30.…”
mentioning
confidence: 99%
“…More than 70% of our patients received mechanical ventilation, which had been associated with a poor prognosis in the literature [36, 37]. The respiratory and cardiovascular components of the SOFA score have been reported to be better predictors than other components of the SOFA score in one ROC analysis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Like another study [ 20 ] which reported that some common etiologies of multiple organ dysfunction—dengue shock syndrome and multiple organ dysfunction syndrome—directly related to the organ failure index present a significant risk of mortality, we found that patients who died had more thoracic (72.2% vs 20.0%), cardiovascular (72.7% vs 17.3%), and multiorgan (93.9% vs 25.5%) failures than did survivors (both P < 0.0001). Other studies have reported that patients who die were more likely to have cardiovascular (100% vs 12%) or respiratory (88% vs 12%) failures than were survivors (both P < 0.01), [ 17 ] that a dengue viral infection with an acute respiratory failure is a significant mortality risk, [ 21 ] and that a lower platelet count before being discharged from the ICU was associated with higher in-hospital mortality. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%